2012
DOI: 10.1007/s11307-012-0562-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Reactive and Tumor Metastatic Lymph Nodes with Diffusion-weighted and SPIO-Enhanced MRI

Abstract: Objectives Determination of lymphatic metastasis is of great importance for both treatment planning and patient prognosis. We aim to distinguish tumor metastatic lymph nodes (TLNs) and reactive lymph nodes (RLNs) with diffusion-weighted and superparamagnetic iron oxide (SPIO) enhanced magnetic resonance imaging (MRI). Materials and methods Ipsilateral popliteal lymph node metastasis or lymphadenitis model was established by hock injection of either luciferase-expressing 4T1 murine breast cancer cells or Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 33 publications
4
39
0
Order By: Relevance
“…After local administration, PET imaging can be performed first to identify the distribution and location of SLNs around the tumor. Then the surgeon can rely on visible blue color and fluorescence imaging One limitation of 18 F-AlF-NEB/EB is that this strategy may not be used directly to visualize tumor metastasis, although increased tracer accumulation can be observed in some tumordraining LNs (32). Indeed, several tumor-draining LNs were not visible on PET images described in this study.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…After local administration, PET imaging can be performed first to identify the distribution and location of SLNs around the tumor. Then the surgeon can rely on visible blue color and fluorescence imaging One limitation of 18 F-AlF-NEB/EB is that this strategy may not be used directly to visualize tumor metastasis, although increased tracer accumulation can be observed in some tumordraining LNs (32). Indeed, several tumor-draining LNs were not visible on PET images described in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Histology showed that these LNs were fully occupied by tumor cells with no lymphatic function and that the afferent lymphatic vessels toward the LNs were blocked by metastatic tumors. It is of note that visualization of tumor-draining LNs using lymphatic mapping agents is time-and stage-dependent (10,32). At the very early stage, when no tumor metastasis exists, the growth of the primary tumor induces a local inflammatory reaction and the tumor-draining LNs undergo hyperplasia, with stimulation of cytokines secreted by the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of lymph node metastasis is crucial in staging breast tumor and for determining adjuvant therapy for the cancer patients (Nakai et al, 2011;Zhang F et al, 2013). Sentinel Lymph Node (SLN) biopsy are invasive conventional imaging technique for lymph node metastasis with many side effects such as morbidity, infection and chronic pain in patients.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Sentinel Lymph Node (SLN) biopsy are invasive conventional imaging technique for lymph node metastasis with many side effects such as morbidity, infection and chronic pain in patients. On the contrary, use of SPION in SLN is less invasive and can differentiate the healthy and metastatic lymph nodes by decreasing the signal intensity (negative contrast) in the non-metastatic lymph nodes (Harada et al, 2007; A C C E P T E D M A N U S C R I P T Motomura et al, 2011;Nakai et al, 2011;Zhang F et al, 2013). USPIO based post contrast MR imaging has been found to be highly effective in detecting metastatic lymph nodes of axilla region even in stage II and III breast cancer patients when compared to conventional MR imaging (Harada et al, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…9). Recently, Zhang and colleagues (10) have reported that both diffusion-weighted and superparamagnetic iron oxide-enhanced MRI can distinguish tumor metastatic lymph nodes from reactive lymph nodes. However, both methods have limited value in detecting microscopic tumor metastasis to the draining lymph nodes at the early stages.…”
Section: Introductionmentioning
confidence: 99%